The Effect of Tapak Liman (Elephantopus scaber L.) Extract on Xa4 Gene Expression in Rice IR64 Infected by Bacterial Leaf Blight (Xanthomonas oryzae) - Hardian Susilo Addy; Wulan Arum Hardiyani; Nur Habibullah; Ali Wafa (International Journal of Secondary Metabolite)
Bacterial leaf blight, caused by Xanthomonas oryzae pv. oryzae (Xoo), represents a significant threat to rice (Oryza sativa) production. Induce plant resistance has emerged as a promising control strategy. The extract of Tapak Liman (Elephantopus scaber) has been considered a promising agent due to its antimicrobial properties, with several of its compounds showing its potential as inducers of plant resistance. This study aimed at elucidating the impact of Tapak Liman extract on the expression of resistance Xa4 gene in rice that plays a crucial role in the synthesis mechanism leading to cell wall thickening. To explore this effect, we analyzed Xa4 gene expression using the reverse transcription-polymerase chain reaction (RT-PCR) technique, followed by a semi-quantitative descriptive analysis. Our results demonstrate that the application of Tapak Liman extracts at a concentration of 10 mg/ml significantly upregulates Xa4 gene expression in the IR64 compared with other concentrations, 1 mg/ml or 5 mg/ml. Furthermore, the observed higher expression of the Xa4 gene persists until 5 days after pathogen inoculation, which is also implicated with a less developed lesion on rice leaves by 76% compared with the control.